2018
DOI: 10.1089/mdr.2017.0263
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Temporal Variation of Extended Spectrum β-Lactamase–Producing Bacteria in Urban Swedish Mallards

Abstract: Antibiotic resistant bacteria present a growing global healthcare challenge. Previous research demonstrates that wild birds harbor extended spectrum β-lactamase (ESBL)-producing Enterobacteriaceae and may contribute to their dissemination. We aimed to assess prevalence and temporal variation in the detection rate of ESBL-producing bacteria in urban wild birds and to evaluate methods regarding sample handling. Monthly fecal sampling was performed in 2013 at an urban pond in Sweden. ESBL-producing Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The present study detected 28.6% ESBL E. coli in common teals ( Anas crecca ). Previous studies indicated a variable prevalence of ESBL-producing bacteria in ducks: 0% in mallards ( Anas platyrhynchos ) in the Czech Republic [ 38 ] and 33.3% (1/3) in mallards in Poland [ 39 ]; 31% ESBL E. coli were reported from multiple migratory bird species, including common teals ( Anas crecca ) in Pakistan with bla TEM dominant gene type [ 40 ] and 47% in ducks in Sweden with bla CTX-M-15 as the dominant ARG [ 41 ]. In 2017, the first preliminary report was published that provided evidence of the existence of ESBL-producing Klebsiella pneumoniae in wild migratory birds in wetlands in Pakistan [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study detected 28.6% ESBL E. coli in common teals ( Anas crecca ). Previous studies indicated a variable prevalence of ESBL-producing bacteria in ducks: 0% in mallards ( Anas platyrhynchos ) in the Czech Republic [ 38 ] and 33.3% (1/3) in mallards in Poland [ 39 ]; 31% ESBL E. coli were reported from multiple migratory bird species, including common teals ( Anas crecca ) in Pakistan with bla TEM dominant gene type [ 40 ] and 47% in ducks in Sweden with bla CTX-M-15 as the dominant ARG [ 41 ]. In 2017, the first preliminary report was published that provided evidence of the existence of ESBL-producing Klebsiella pneumoniae in wild migratory birds in wetlands in Pakistan [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the prevalence of ESBL-producing K.pneumoniae was 43.5% (95% CI 39.3-47.9%) among clinical K. pneumoniae isolates (Beigverdi et al, 2019a). In a study from Sweden in 2018, Hessman et al (2018) reported that only 2% of K. pneumoniae isolates produced ESBLs. In Spain, the prevalence of ESBL-producing K. pneumoniae in 2017 was 7.2% (Cubero et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-15 is the main CTX-M-type of clinical ESBLproducing K. pneumoniae in China and other parts of the world. [31][32][33][34][35][36][37] Furthermore, bla CTX-M-15 -positive K. pneumoniae has been also widely detected in various animals, including farm cattle, pet dogs, and wild birds, [38][39][40] indicating communication between the genetic pools of the bla CTX-M-15 gene in animals and humans. In future studies, we should investigate how these ESBLs are transmitted from animals to humans, and then implement measures to block this route to avoid such infections and outbreaks.…”
Section: Discussionmentioning
confidence: 99%